Synaptic Vesicle Proteins and Active Zone Plasticity - Kittel, Robert J.; Heckmann, Manfred (Frontiers in Synaptic Neuroscience, 2016)
Neurotransmitter is released from synaptic vesicles at the highly specialized presynaptic active zone (AZ). The complex molecular architecture of AZs mediates the speed, precision and plasticity of synaptic transmission. Importantly, structural and functional properties of AZs vary significantly, even for a given connection. Thus, there appear to be distinct AZ states, which fundamentally influence neuronal communication by controlling the positioning and release of synaptic vesicles. Vice versa, recent evidence has revealed that synaptic vesicle components also modulate organizational states of the AZ. The protein-rich cytomatrix at the active zone (CAZ) provides a structural platform for molecular interactions guiding vesicle exocytosis. Studies in Drosophila have now demonstrated that the vesicle proteins Synaptotagmin-1 (Syt1) and Rab3 also regulate glutamate release by shaping differentiation of the CAZ ultrastructure. We review these unexpected findings and discuss mechanistic interpretations of the reciprocal relationship between synaptic vesicles and AZ states, which has heretofore received little attention.